Epilepsy and adverse quality of life in surgically resected meningioma. (14th November 2016) - Tanti, M. J.; Marson, A. G.; Jenkinson, M. D.
Abstract : Objectives: Meningiomas are common intracranial tumors, and despite surgery or therapy with anti‐epileptic drugs (AEDs), many patients suffer from seizures. Epilepsy has a significant impact on quality of life (QoL) in non‐tumor populations, but the impact of epilepsy on QoL in patients with meningioma is unknown. Our aim was to evaluate the impact of epilepsy on QoL in patients that have undergone resection of a benign meningioma. Materials and Methods: We recruited meningioma patients without epilepsy (n=109), meningioma patients with epilepsy (n=56), and epilepsy patients without meningioma (n=64). QoL was measured with the Short Form 36 version 2 (SF‐36), the Functional Assessment of Cancer Therapy (FACT‐BR), and the Liverpool Adverse Events Profile (LAEP). Regression analyses identified significant determinants of QoL. Results: Patients with meningioma and epilepsy had poorer QoL scores than meningioma patients without epilepsy in all measures. In FACT‐BR, this difference was significant. Multiple regression analyses demonstrated that current AED use had a greater impact on QoL scores than recent seizures. Other variables associated with impaired QoL included depression, unemployment, and meningioma attributed symptoms. Conclusions: Epilepsy has a negative impact on quality of life in patients with benign meningioma. AED use is correlated with impaired QoL and raised LAEP scores, suggesting that AEDs and adverse effects may have led to impaired QoL in our meningioma patients with epilepsy. The severity of epilepsy in our meningioma population was comparatively mild; therefore, a more conservative approach to AED therapy may be indicated in an attempt to minimize adverse effects.